The Representation of Women in Bertolt Brecht’s Play - Haryati, Isti (Future Science)
This study aims to describe the portrayal of women in Bertolt Brecht's dramas. In his plays, Brecht's women descriptions are different from the typical characteristics of his time. By looking at the way he portrayed the female characters, Bertolt Brecht's purpose can be identified. The data sources of this study are three Bertolt Brecht’s dramas, namely Die Dreigroschenoper, Mutter Courage und Ihre Kinder, and Der Gute Mensch von Sezuan. Marxist feminist literary theory is used to analyze the data. The results show that the women in Brecht's drama are described as strong and independent women. Polly Peachum and Mrs. Peachum in Die Dreigroschenoper are independent women who work to help her husband in managing the business. Mutter Courage in Mutter Courage und Ihre Kind shows an independent woman who draws some money on the battlefield. Shen Te in Der Gute Mensch von Sezuan is a beautiful woman who was chosen by God as a good person and tries hard to open a business. From the portrayal of these women, it is comprehended that the women figures created by Brecht have different characters. They are eager to act and fight against the injustice against women and the classism factor. Despite their social class and gender being weak, they can rise and show their existence to prevent themselves from oppression. Brecht’s Marxist ideology preceded the portrayal of the female characters in his dramas.